2014
DOI: 10.1016/j.ymeth.2013.07.040
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing the quantitative accuracy and reproducibility of Förster resonance energy transfer measurement for screening by high throughput widefield microscopy

Abstract: Förster resonance energy transfer (FRET) between fluorescent proteins (FPs) provides insights into the proximities and orientations of FPs as surrogates of the biochemical interactions and structures of the factors to which the FPs are genetically fused. As powerful as FRET methods are, technical issues have impeded their broad adoption in the biologic sciences. One hurdle to accurate and reproducible FRET microscopy measurement stems from variable fluorescence backgrounds both within a field and between diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The AR BioAssay used here quantifies the androgen-mediated movement of a fluorescent protein (FP)-tagged human AR from the cytoplasm to the cell nucleus and was previously developed for high throughput quantification of AR response to androgenic drugs [ 26 , 29 ]. That AR BioAssay consists of a HeLa cell line that stably expresses the yellow FP (YFP)-tagged AR together with an mCherry-NLS-mCherry construct (where NLS is nuclear localization signal).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The AR BioAssay used here quantifies the androgen-mediated movement of a fluorescent protein (FP)-tagged human AR from the cytoplasm to the cell nucleus and was previously developed for high throughput quantification of AR response to androgenic drugs [ 26 , 29 ]. That AR BioAssay consists of a HeLa cell line that stably expresses the yellow FP (YFP)-tagged AR together with an mCherry-NLS-mCherry construct (where NLS is nuclear localization signal).…”
Section: Resultsmentioning
confidence: 99%
“…One day following the addition of urine, green fluorescence from the YFP-tagged AR and red fluorescence from the mCherry-linked nuclear marker were collected on an IXMicro High Throughput Microscope (Molecular Devices Corp., Sunnyvale, CA, USA) using filter sets previously described [ 29 ] and a 10x objective that our prior studies had shown to maximize the numbers of cells collected in a field at a magnification sufficient to distinguish the margins of adjacent cell nuclei and enable accurate image analysis [ 26 , 29 ]. Although the CFP-AR-YFP reporter also expresses CFP, CFP fluorescence was not quantified because the loss of CFP fluorescence by energy transfer to YFP changes with the types of AR ligands available [ 26 , 35 , 45 , 46 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We believe that this limitation on the design pallet available to biosensor developers arises primarily because of a lack of instrumentation that can 1: rapidly & reliably, and 2: simultaneously measure multiple photo-physical changes in biosensors. Automated microscopes 11 15 have been developed to address the first issue, but robotic systems that can concurrently monitor multiple photo-physical properties have not been reported. In this paper, we describe the design, construction, and utility of an automated multi-modal microscope that simultaneously measures fluorescence intensity (photon count), lifetime, time-resolved anisotropy, molecular brightness, concentration, and lateral diffusion.…”
Section: Introductionmentioning
confidence: 99%